ANALISIS TINGKAT KEPUASAN PENUMPANG ANGKUTAN UMUM ANTAR KOTA PT. SARAH NURSYIFA TRANSPORT RUTE TANJUNG PATI – PADANG - Ramadhan, Andre; Kurniawan, Deddy; Bastian, Elfania (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Transportation is the activity of moving passengers or goods from one place to another. So far, PT Sarah Nursyifa Transport on the Tanjung Pati - Padang route has become one of the types of transport of interest to the community. With the increasing mobility of the population, the availability of adequate transportation facilities and infrastructure is required, so that inter-city public transportation services are needed that meet the good and proper requirements for passengers. In this thesis using the Likert scale method. By circulating a questionnaire of 100 respondents. This research was conducted by survey through distributing questionnaires to respondents. After that, testing the validity and reliability of the questionnaire is carried out, then proceed with data analysis of the research results. From the results of data analysis, it was obtained that the analysis of the level of satisfaction of PT. Sarah Nursyifa Transport bus public transportation passengers according to the community with a value of 19% with Very Good criteria, 47% with good criteria, 28% with Less Good criteria and 6% with Not Good criteria. The results of the analysis of 20 respondents obtained the smallest reliability value of 0.621 and the largest reliability of 0.89. This value. While analyzing the respondents as many as 20 people got r count with the smallest value of 0.621> r table with a value of 0.255, it can be said that the data is valid.Keywords: Passenger Satisfaction Level, Validity, Reliability